Diversity of Nuclear Lamin A/C Action as a Key to Tissue-Specific Regulation of Cellular Identity in Health and Disease - Malashicheva, Anna; Perepelina, Kseniya (Frontiers in Cell and Developmental Biology, 2021)
A-type lamins are the main structural components of the nucleus, which are mainly localized at the nucleus periphery. First of all, A-type lamins, together with B-type lamins and proteins of the inner nuclear membrane, form a stiff structure—the nuclear lamina. Besides maintaining the nucleus cell shape, A-type lamins play a critical role in many cellular events, such as gene transcription, epigenetic regulation, cell migration and cell differentiation. Lamin A/C multifunctionality is achieved due to their direct and indirect interactions with inner nuclear membrane proteins, transcription factors and signaling molecules, as well as their participation in chromatin organization. Large chromatin regions interacting with nuclear lamina, known as lamina-associated domains (LADs), are unique for various cell types. Genes included in LADs are transcriptionally repressed; however, some LADs are repositioned away from or towards the lamina during cell differentiation in a tissue-specific manner. Spatiotemporal changes in lamin–chromatin interaction have a tissue-specific and cell cycle-dependent character. Proper lamin A/C framework is critical for genome function, cellular identity, and developmental potential. In addition, cooperation of lamin A/C with important signaling pathway (Rb/E2F, Wnt/β-catenin, TGFβ, Notch, etc.) components is significant for the cell’s fate and differentiation process. Mutations in the LMNA gene coding lamin A/C lead to changes in spatial LADs organization. Consequently, the cell's expression profile for fate genesis is changed, which could lead to differentiation contravention in stem cells. In this review we have summarized recent data focused on lamin A/C action mechanisms in regulation of cell differentiation and identity development of stem cells of different origin. We also discuss how this knowledge can promote further research towards a deeper understanding of the role of lamin A/C mutations in laminopathies.